2020
DOI: 10.3238/arztebl.2020.0253
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification of Self-Reported Body Mass Index Categories

Abstract: verweight and obesity are a growing global public health problem (1). Epidemiological analyses have projected that overweight will be one of the top 4 global causes of preventable years of life lost in the future, besides hypertension, diabetes, and smoking (2). Already in 2007, the social costs of overweight amounted to 16 billion Pound Sterling in the United Kingdom (corresponding to 1% of their gross national product), with a strong upward trend. According to guideline recommendations on the prevention of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 56 publications
5
23
0
Order By: Relevance
“…This misperception was most pronounced in obese participants: 67.6% of obese participants misclassified their weight compared to 36.2% of overweight participants, 33.9% of normal weight participants, and 34.3% of underweight participants. About 8.4% of the obese participants in this study perceive themselves to be underweight or normal weight, which is similar to previous studies where the most common misclassification among obese participants was underestimation [25]. In line with Saudi Arabian [21] and international studies (25), our findings indicate that obese individuals are particularly vulnerable to weight misperception.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This misperception was most pronounced in obese participants: 67.6% of obese participants misclassified their weight compared to 36.2% of overweight participants, 33.9% of normal weight participants, and 34.3% of underweight participants. About 8.4% of the obese participants in this study perceive themselves to be underweight or normal weight, which is similar to previous studies where the most common misclassification among obese participants was underestimation [25]. In line with Saudi Arabian [21] and international studies (25), our findings indicate that obese individuals are particularly vulnerable to weight misperception.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous studies, we observed a significant association between age and weight perception, with older adults more likely to misperceive their weight than their younger peers [25]. Older adults were also more likely to be overweight and obese, which may contribute in part to the observed relationship between age and weight misperception.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of measured overweight or obesity (BMI ≥ 25) was nearly 60% in men and 30% in women, but more than half of those underreported their weight group when asked about this, especially the men (60% versus 40%, respectively). This is consistent with the results from a recent systematic review of more than 50 studies from 25 countries (n = 174,000), concluding that self-perceived BMI group is often incorrect, with underreporting being more prevalent than overreporting [27]. Comparable to our findings, others have also reported that men and those with a high BMI (≥25) were more likely to underreport than women and normal weight participants [27,31,45], a result that may to some degree be explained by the higher proportion of men (58%) than women (33%) in the high BMI category (≥25).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results from a recent systematic review of more than 50 studies from 25 countries (n = 174,000), concluding that self-perceived BMI group is often incorrect, with underreporting being more prevalent than overreporting [27]. Comparable to our findings, others have also reported that men and those with a high BMI (≥25) were more likely to underreport than women and normal weight participants [27,31,45], a result that may to some degree be explained by the higher proportion of men (58%) than women (33%) in the high BMI category (≥25). Nevertheless, maintaining or reaching a healthy body weight is important for disease prevention and overall health [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation